2021
DOI: 10.3390/ijerph19010222
|View full text |Cite
|
Sign up to set email alerts
|

Association of Psychological Resilience with All-Cause and Cardiovascular Mortality in a General Population in Italy: Prospective Findings from the Moli-Sani Study

Abstract: Psychological resilience (PR) is the capacity to adapt positively in face of adversity. Its role as an independent protective factor has been acknowledged in recent years. We aimed to test the association of PR with all-cause and cardiovascular disease (CVD) mortality in a general adult population. We performed longitudinal analyses on 10,406 CVD-free individuals from the Moli-Sani cohort (follow up = 11.2 year). PR was assessed by the 25-item Connor and Davidson resilience scale. PR factors were identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, much less is known about negative metabolic outcomes of stress among individuals with varying stress resiliency. It has been shown that stress-sensitive individuals are at higher risk of developing chronic diseases, whereas increased resiliency is associated with improved health, quality of life, and reduced mortality [13,14]. However, data on the link between stress resiliency and metabolic health are still limited, and the mechanisms are undefined.…”
Section: Introductionmentioning
confidence: 99%
“…However, much less is known about negative metabolic outcomes of stress among individuals with varying stress resiliency. It has been shown that stress-sensitive individuals are at higher risk of developing chronic diseases, whereas increased resiliency is associated with improved health, quality of life, and reduced mortality [13,14]. However, data on the link between stress resiliency and metabolic health are still limited, and the mechanisms are undefined.…”
Section: Introductionmentioning
confidence: 99%